2015
DOI: 10.1371/journal.ppat.1004820
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-Induced Necroptosis Is a Major Mechanism of Staphylococcus aureus Lung Damage

Abstract: Staphylococcus aureus USA300 strains cause a highly inflammatory necrotizing pneumonia. The virulence of this strain has been attributed to its expression of multiple toxins that have diverse targets including ADAM10, NLRP3 and CD11b. We demonstrate that induction of necroptosis through RIP1/RIP3/MLKL signaling is a major consequence of S. aureus toxin production. Cytotoxicity could be prevented by inhibiting either RIP1 or MLKL signaling and S. aureus mutants lacking agr, hla or Hla pore formation, lukAB or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
251
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 218 publications
(269 citation statements)
references
References 53 publications
10
251
1
Order By: Relevance
“…While the importance of neutrophils in the response to S. aureus is well established, PVL targeting of macrophages correlated with the pulmonary pathology due to S. aureus infection, as has been demonstrated in other recent studies [19]. This is also consistent with recent studies that demonstrated that S. aureus induction of murine macrophage necroptosis in the early stages of pneumonia resulted in the loss of the immunomodulatory population of macrophages and contributed to the excessive inflammatory responses associated with S. aureus pneumonia [19]. Macrophages can play both proinflammatory and antiinflammatory roles and thus have many functions within the host [40].…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…While the importance of neutrophils in the response to S. aureus is well established, PVL targeting of macrophages correlated with the pulmonary pathology due to S. aureus infection, as has been demonstrated in other recent studies [19]. This is also consistent with recent studies that demonstrated that S. aureus induction of murine macrophage necroptosis in the early stages of pneumonia resulted in the loss of the immunomodulatory population of macrophages and contributed to the excessive inflammatory responses associated with S. aureus pneumonia [19]. Macrophages can play both proinflammatory and antiinflammatory roles and thus have many functions within the host [40].…”
Section: Discussionsupporting
confidence: 68%
“…Macrophages can play both proinflammatory and antiinflammatory roles and thus have many functions within the host [40]. Their loss can prevent proper bacterial clearance [19,20], while their signaling cascades can contribute to inflammation and inefficient clearance [19]. Our results from the humanized mice suggest that human macrophages are especially susceptible to PVL-mediated lysis in vivo.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations